Analisis Minat Belajar Siswa Kelas X pada Pembelajaran Akidah Akhlak Pendidikan Agama Islam - Siti Maryani; Achmad Junaedi Sitika; Ceceng Syarief (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2021)
In the context of the analysis of the learning process of aqidah akhlaq Islamic religious education in class X students, the interaction process of students experienced a decrease who were less motivated in learning aqidah. This study reveals that if you want to increase students' interest in learning in class X, and the spirit of students' learning activities, the teacher's ability to provide learning motivation and also student learning responses through class lessons. This research also aims to be able to regenerate interest in student learning, to find out how students' learning activities are, the teacher's ability to provide development and direction about interest in learning, and also to know the learning responses of students through classroom learning. The strategy that can be applied as a teacher is through classroom learning so that the effectiveness of students in being interested in learning Aqidah Akhlah & PAI is better than before. However, teachers as teachers are also required to have creativity and interesting innovations if they want to create a conducive and effective learning atmosphere. Abstrak Dalam konteks analisis proses pembelajaran aqidah akhlaq pendidikan agama Islam pada peserta didik kelas X proses interaksi peserta didik mengalami penurunan yang kurang termotivasi dalam belajar aqidah. Penelitian ini mengungkapkan bahwa jika ingin meningkatkan minat belajar peserta didik di kelas X ini, dan jiwa aktivitas belajar peserta didik, kemampuan guru pun dalam memberikan motivasi belajar dan juga respon belajar peserta didik melalui pelajaran di kelas. Penelitian ini pula bertujuan untuk dapat menumbuhkan kembali minat pada pembelajaran peserta didik, untuk mengetahui bagaimana aktivitas belajar peserta didik, kemampuan guru dalam memberikan pengembangan dan arahan tentang minat belajar, dan juga mengetahui responsi belajar peserta didik melalui pembelajaran di kelas. Strategi yang dapat diterapkan sebagai guru ialah melalui pembelajaran di kelas sehingga efektivitas peserta didik dalam berminat untuk belajar Aqidah Akhlah & PAI menjadi lebih baik daripada sebelumnya. Namun juga demikian, guru sebagai pengajar juga dituntut untuk memiliki kreativitas serta inovasi yang menarik jika ingin menciptakan suasana pembelajaran yang kondusif dan efektif.